Acupuncture Combined with Bushen-Jianpi Decoction Ameliorates the Ovarian Function of Diminished Ovarian Reserve Rats by Regulating Phosphoinositide 3-Kinase/AKT Signaling - Lao, Jianting; Hu, Panwei; Li, Jia; Li, Jiahui; Zhang, Xiaole; Yang, Hong; Qi, Cong (Combinatorial Chemistry & High Throughput Screening, 2024)
Objective: This study aimed to explore the therapeutic efficiency as well as mechanism of acupuncture combined with Bushen-Jianpi decoction (BJD) to treat rats with diminished ovarian reserve (DOR). Methods: A DOR rat model was constructed using zona pellucida 3 peptide, and acupuncture, BJD, and their combination were administered as therapeutic interventions. We measured changes in the ovarian indexes, the number of follicles at all levels, the serum levels of sex hormones and immune factors, the expression levels of phosphoinositide 3-kinase (PI3K), AKT, p-AKT, and caspase-3, and the changes in the proportions of splenic T cell subtypes, including T-helper 17 (Th17), Tc17, regulatory T (Treg), CD4+, and CD8+ cells. Results: Acupuncture combined with BJD induced a decrease in the levels of follicle-stimulating and luteinizing hormones, and the effect was greater than that elicited by BJD or acupuncture alone (P < 0.05). Additionally, this combination treatment effectively abrogated the increase in the levels of interleukin-2 (IL-2), IL-17, anti-zona pellucida antibody, and cleaved caspase-3 (P < 0.05), while promoting the regulation of IL-6 and p-AKT (P < 0.01). Furthermore, treatment with acupuncture combined with BJD restored the proportions of CD4+ cells and the CD4+ / CD8+ T cell ratio (P < 0.01), decreased the proportion of CD8+ T and Th17 cells (P < 0.01), and increased the proportions of Tc17 and Treg cells (P < 0.01). Conclusion: Combining acupuncture with BJD can enhance ovarian function in DOR rats. The regulation of sex hormone levels and immune function in rats may be attributed to the adjustment of the mRNA and proteins levels of PI3K, AKT, and caspase-3 in the PI3K/AKT signaling pathway, which leads to an improvement in the immune function of DOR rats.
Keywords: diminished ovarian reserve